A Boa Aula na perspectiva dos alunos do Ensino Técnico Integrado ao Médio - Ribeiro, Samuel de Almeida (2019)
This paper aimed at analyzing good teacher practices from the perspective of Technical Programs Integrated to High School (Ensino Técnico Integrado ao Médio – ETIM) students. Thus, specific objective was to unveil characteristics of a GOOD CLASS through the eyes of ETIM students, in order to contribute for teachers’ reflecting about their practices. We have intended to acknowledge good teacher practices, the object of this study, in order to foster reflection about their actions. For theoretical background, we have used Social Representations Theory (RS) as proposed by Moscovici (1961), which has enabled us to unveil, within students’ speeches, the representations built towards their teachers. For data collection instrument, we have used Free Word Association Technique (TALP), using “GOOD CLASS” as inductive stimulus. TALP has been applied to a group of 75 students: 41 from a technical school located in the East Zone of the city of São Paulo (SP) and 34 from a technical school located in the South Zone of the same city. For data tabulation and analysis, we have made use of the software EVOC, which has enabled us to identify the characteristics students attribute to a GOOD CLASS through their answers and justifications. Analysis of the words selected by EVOC have indicated that students represent the teacher as the one who defines, establishes and conducts the GOOD CLASS. In these terms, given the importance attributed to the teacher by the students, although the object of study was the GOOD CLASS, it could not be analyzed, from the students’ perspective, without the teacher. For the students, GOOD CLASS is the way teachers conduct their activities in the classroom; it is more than an attribute to their performance. Thus, according to students’ representations, the GOOD CLASS has not been analyzed as an independent object, i.e., as an action which is independent of the subject who performs it. It has been clear, in this study, that the teacher is, for these students, the primary protagonist of the GOOD CLASS. This research offers elements to orient teachers’ work in the classroom and, at the same time, to articulate students’ participation and protagonism through the educational process while conducting a GOOD CLASS